2015
DOI: 10.1097/mcg.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Over 3-branched Partial Stent-in-Stent Drainage Using Self-expandable Metallic Stents in Patients With Unresectable Hilar Biliary Carcinoma

Abstract: The use of endoscopic over 3-branched biliary drainage with a SEMS may improve the duration of patency in patients with HBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Inoue et al ( 35 ) reported the insertion of three SEMSs, where the combination of the placement of stent-in-stent SEMSs and side-by-side SEMSs was performed. In a report written by Uchida et al ( 20 ), more than three-branched drainage improved the duration of patency in patients with unresectable hilar biliary carcinoma. In that report, six patients received four SEMSs using 7- or 8-Fr devices.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inoue et al ( 35 ) reported the insertion of three SEMSs, where the combination of the placement of stent-in-stent SEMSs and side-by-side SEMSs was performed. In a report written by Uchida et al ( 20 ), more than three-branched drainage improved the duration of patency in patients with unresectable hilar biliary carcinoma. In that report, six patients received four SEMSs using 7- or 8-Fr devices.…”
Section: Discussionmentioning
confidence: 96%
“…We experienced a case in which four uncovered SEMSs were inserted to treat liver abscess. In a retrospective study, six patients with hilar biliary obstruction in whom four uncovered SEMSs were placed were reported ( 20 ). However, the details concerning the insertion of the four uncovered SEMSs were not described.…”
Section: Introductionmentioning
confidence: 99%
“…reported a pioneering study on the placement of three or more SEMS in 2007, where they demonstrated nine successful cases of placement by the SIS method. In 2015, Uchida et al . reported a retrospective study comparing placement of three or more SEMS with placement of two or less.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamoto et al 9 reported a pioneering study on the placement of three or more SEMS in 2007, where they demonstrated nine successful cases of placement by the SIS method. In 2015, Uchida et al 20 reported a retrospective study comparing placement of three or more SEMS with placement of two or less. They found that the patency period and survival in the three or more stents group was significantly longer than that in the two or fewer stents group among the patients achieving disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of multiple metal stents (MS) for the management of high‐grade malignant hilar biliary obstruction (MHBO) is useful, and biliary radiofrequency ablation (RFA) has been suggested to improve stent patency . However, to our knowledge, there are no reports of RFA procedures carried out using a single‐balloon endoscope (SBE) in patients with surgically altered anatomy.…”
Section: Brief Explanationmentioning
confidence: 99%